2019
DOI: 10.1021/acs.analchem.9b00204
|View full text |Cite
|
Sign up to set email alerts
|

An Autonomous Microfluidic Device for Generating Volume-Defined Dried Plasma Spots

Abstract: Obtaining plasma from a blood sample and preparing it for subsequent analysis is currently a laborious process involving experienced health-care professionals and centrifugation. We circumvent this by utilizing capillary forces and microfluidic engineering to develop an autonomous plasma sampling device that filters and stores an exact amount of plasma as a dried plasma spot (DPS) from a whole blood sample in less than 6 min. We tested 24 prototype devices with whole blood from 10 volunteers, various input vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…22 Several microsampling devices have been developed to collect a fixed volume of plasma from finger-prick blood without centrifugation. [28][29][30] The combination of these devices with our method would be an option to conduct routine TDM based on DPS prepared at patients' homes.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several microsampling devices have been developed to collect a fixed volume of plasma from finger-prick blood without centrifugation. [28][29][30] The combination of these devices with our method would be an option to conduct routine TDM based on DPS prepared at patients' homes.…”
Section: Discussionmentioning
confidence: 99%
“…The excess plasma is removed through the drainage valve. 92,93 Some proof-of-principle measurements demonstrated the capability of the device to generate DPS of a fixed volume, within a limited Hct range (39%-45%) and a blood input volume range of 40-80 mL. This initial evaluation also revealed that, compared with plasma obtained through centrifugation, 73% 6 8% of the plasma proteins were recovered after filtration of venous and capillary blood.…”
Section: Autonomous Microfluidic Dps Devicementioning
confidence: 97%
“…The devices were fabricated using lamination technology where the device is formed by stacking several layers of different materials, as described previously. 17,18 The cross section in Fig. 1a shows the different layers.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The PVA film was fabricated, as previously reported, 17,18 from an aqueous solution of 20 wt% of granular PVA. Using a thin-film applicator (4340, Elcometer, Manchester, UK) the PVA films were uniformly transferred to laminating pouches (3385694, Office Depot, LA Venlo, Netherlands) and dried at room temperature.…”
Section: Device Fabricationmentioning
confidence: 99%